A New Technique for Patient Registration During Navigated Total Hip Arthroplasty. Issue 4 (December 2021) - Oragui, Emeka; Du-Moulin, Will; Adie, Sam; Molnar, Robert; Harris, Laura
Abstract : Background: This study describes a new technique of computer navigation for total hip arthroplasty (THA) that uses a customized perspex board to register the coronal plane of a patient in the lateral position. Cup placement is then referenced to the coronal plane. Purposes: This paper looks at the outcome of this technique. Materials and Methods: Seventeen patients who underwent a total of 18 THA were included. During surgery, the patient was placed in a lateral decubitus position and care taken to ensure the patient was secured perpendicular to the table. The coronal plane was registered using a customized perspex board aligned with the long axis of the operating table. The intraoperative target for acetabular cup placement was 20-degree anteversion and 40-degree inclination with respect to the coronal plane. Radiographs were taken 6 weeks postoperatively. Results: The mean cup angle of anteversion was larger in the postoperative method ( M =22.83, SD=4.436) than in the intraoperative method ( M =22.39, SD=4.629). A 1-sample t test indicated the difference between means was not statistically significant. The mean cup angle of inclination was larger in the intraoperative method ( M =44.83, SD=3.400) than in the postoperative method ( M =41.56, SD=4.693). A 1-sample t test indicated the difference between means was significant although still within the prescribed safe zones. Conclusion: Using a customized perspex board to register the patient and targeting cup placement to a safe zone referenced to the coronal plane result in optimal cup placement when assessed by postoperative radiographs. This avoids the need to turn the patient after registration and obviates the effect of pelvic tilt on cup placement. Level of Evidence: Level IV—case series.